Functional transposition of TILL and UNTIL from a diachronic perspective - Yurii Kovbasko (ExELL (Explorations in English Language and Linguistics))
The research traces the development of functional transposition of TILL and UNTIL in Eng-lish. The study covers 16 historical periods and is based on 1,243 examples extracted from the writings from 850 to 1710, which are analyzed without resorting to any corpus soft-ware; 2,225 examples from 1710 to 1920, which are automatically tagged utilizing the corpus toolbox Lancsbox; and the statistical data on 127,544 examples over the period of 1920–2020. It is hypothesized that despite being synonyms and representatives of the same grammatical categories of prepositions and conjunctions in modern English, the lexical units TILL and UNTIL were initially formed as prepositions and later, following their own trans-positional patterns, they were transposed into conjunctions.